2011
DOI: 10.5037/jomr.2011.2304
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestations of T-Cell Large Granular Lymphocytic Leukemia: a Case Report

Abstract: BackgroundT-cell large granular lymphocytic (T-LGL) leukemia is a rare, chronic, often indolent lymphoproliferative disorder of mature T cells (CD3+). Severe neutropenia and other cytopenias are common features in patients with T-LGL leukemia and may cause infections, thus representing a major cause of morbidity in this disease. Immunosuppressive therapy with low-dose regimes of methotrexate, cyclophosphamide, corticosteroids or cyclosporine A is the treatment of choice. Amongst the variety of T-LGL leukemia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
2
5
0
2
Order By: Relevance
“…In 2000, Copete and Sheridan 3 concluded that it was still unclear whether ulcerations in the oral cavity of patients undergoing leukemia treatment were caused by infective etiology or they were manifestations of neutropenia. The same was concluded by Arvanitidou et al 4 in 2011. It seems that the degree of susceptibility to infection is roughly proportional to the blood neutrophil count.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…In 2000, Copete and Sheridan 3 concluded that it was still unclear whether ulcerations in the oral cavity of patients undergoing leukemia treatment were caused by infective etiology or they were manifestations of neutropenia. The same was concluded by Arvanitidou et al 4 in 2011. It seems that the degree of susceptibility to infection is roughly proportional to the blood neutrophil count.…”
Section: Introductionsupporting
confidence: 84%
“…To prevent abnormal increases in such bacteria on the gingiva, scaling and/or root planing together with local antiseptic and local/systemic antibiotic may contribute to infection control in such patients. This is sometimes impossible as patients may have severe neutropenia or thrombocytopenia, as seen in our case, as well as in cases reported by Arvanitidou et al 4 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Außerdem gibt es zahlreiche paraneoplastische Symptome bei der LGL-Leukämie, darunter B-Zell-Krankheiten (zum Beispiel die Monoklonale Gammopathie unklarer Signifikanz [MGUS]) und Zytopenien (hauptsächlich Neutropenie) [5]. Wenn auch selten berichtet, können Ulzerationen der Haut oder der Mundhöhle mit einem Pyoderma-gangraenosum-artigen Erscheinungsbild auftreten [5,[10][11][12]. Klinische, histologische und immunhistologische Untersuchungen bei unserem und einem früheren Fall [10] legen nahe, dass der ulzerative Prozess möglicherweise auf eine mikrovaskuläre Schädigung, verursacht durch eine intravaskuläre Ansammlung von T-LGLs in der Dermis, zurückzuführen ist.…”
unclassified